2007
DOI: 10.1093/bja/aem203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total intravenous anaesthesia and balanced anaesthesia on the frequency of coughing during emergence from the anaesthesia

Abstract: During emergence from anaesthesia in the knee-elbow position, TIVA is associated with significantly less coughing and reduced haemodynamic response when compared with BAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 30 publications
0
58
1
1
Order By: Relevance
“…Numerous strategies have been used to prevent haemodynamic responses caused by emergence from anaesthesia including extubation under deep anaesthesia, administration of local anaesthetics, vasodilators and short-acting opioids. 22 Administering vasodilators such as sodium nitroprusside, nitroglycerin, and hydralazine could be associated with complications like reflexive tachycardia and increase in the plasma renin activity. 23 Dexmedetomidine may be useful as an effective agent for blunting the adverse haemodynamic and recovery response to tracheal extubation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous strategies have been used to prevent haemodynamic responses caused by emergence from anaesthesia including extubation under deep anaesthesia, administration of local anaesthetics, vasodilators and short-acting opioids. 22 Administering vasodilators such as sodium nitroprusside, nitroglycerin, and hydralazine could be associated with complications like reflexive tachycardia and increase in the plasma renin activity. 23 Dexmedetomidine may be useful as an effective agent for blunting the adverse haemodynamic and recovery response to tracheal extubation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained because of the use of propofol and the larger dose of fentanyl administered during operations, which reduced stimulation during extubation. Hohlrieder et al 11 found that TIVA is associated with significantly less coughing and reduces hemodynamic response when compared with inhalation anesthesia in elective lumbar disc surgery during emergence from anesthesia. In addition, Wang et al 21 demonstrated more stable hemodynamics in the TCI patient group and significantly lower mean arterial pressure and faster recovery profiles compared with the fentanyl/DES patient group.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent a high dynamic response and choking in the recovery process of general anesthesia and extubation, many methods, such as deep anesthesia extubation, the use of local anesthetics, vasodilators, short-acting opioid drugs, and other methods, have been used in the clinic (Shajar et al, 1999;Hohlrieder et al, 2007). Studies have reported that the application of general anesthesia with propofol or remifentanil could make the recovery process of patients smoother (Shajar et al, 1999;Wilhelm et al, 2001;Blayney et al, 2003;Hohlrieder et al, 2007). However, propofol and remifentanil, which are more conducive to allowing patients to pass through the recovery period safely, have been less characterized.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially common in patients with obesity, hypertension, or cardiovascular disease, and can lead to fatal consequences. In order to prevent the highly dynamic response and choking during the extubation period after general anesthesia, many methods such as deep anesthesia extubation, the use of local anesthetics, vasodilators, short-acting opioid drugs, and other methods have been used in the clinic (Hohlrieder et al, 2007). Propofol, an intravenous anesthetic commonly used in the clinic, has a good sedative effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation